Efektivitas Bahan Pembenah Tanah pada Dinamika Fosforus dengan Perunutan Isotop 32P dan Hasil Jagung di Ultisol Jasinga - Nur Robifahmi; Muftia Hanani; Taufiq Bachtiar; Anggi Nico Flatian (Jurnal Ilmu Pertanian Indonesia, 2024)
Soil conditioners can accelerate the recovery of soil physical, chemical, and/or biological quality, thus optimizing soil productivity. The 32P isotope tracing technique was used to determine the contribution of P from soil amendments in the form of lime, biochar, and compost, as well as to study their effects on P fertilization efficiency and corn yield. The treatments included lime, biochar, compost, and combinations of these three materials. The parameters analyzed were corn yield and P contribution from P sources. This study aimed to evaluate the ability of soil amendments to increase P uptake, growth, and yield of corn, as well as to determine the P contribution from lime, biochar, and compost to corn plants using the 32P isotope tracing technique. The results on Ultisol soil from Jasinga, Bogor, showed that the combination of 3 t ha-1 lime + 15 t ha-1 biochar + 15 t ha-1 compost resulted in the highest grain weight of 45.942 g per plant; the contribution of P from the carrier materials to the grain of the combination of 3 t ha-1 lime + 15 t ha-1 biochar + 15 t ha-1 compost was 44.945 mg per plant. In conclusion, the combination of these soil conditioners can increase P availability and corn production on Ultisol soil from Jasinga, Bogor. Keywords: soil conditioner material, 32P isotope tracer technique, Ultisols